Upland rice seedling performance promoted by multifunctional microorganisms - Fernandes, João Pedro Tavares; Nascente, Adriano Stephan; Filippi, Marta Cristina Corsi de; Silva, Mariana Aguiar (Semina: Ciências Agrárias, 2021)
Multifunctional microorganisms can contribute to the development of plant root systems and positively affect the grain yield of crops. However, studies of the use of these microorganisms to benefit root development in rice plants are scarce. The objective of this study was to determine the effect of rhizobacterial inoculation of the seeds on the root development of upland rice seedlings. The experiment was carried out in the agricultural microbiology laboratory of Embrapa Rice and Beans, and we adopted a completely randomized design with eight replications. The treatments consisted of the inoculation of rice seeds with the rhizobacteria 1. Pseudomonas fluorescens (BRM 32111), 2. Burkholderia pyrrocinia (BRM 32113), 3. Serratia sp. (BRM 32114), 4. Bacillus sp. (1301), 5. Azospirillum brasilense (Ab-V5), 6. Azospirillum sp. (1381), and a 7. control treatment (without microorganisms). Treatment using the microorganism Azospirillum sp. (1381) provided the longest roots, greatest root volume and highest total dry mass of roots, at 86.34, 111.53 and 29.41%, respectively, significantly superior to the control treatment. In addition, treatments Ab-V5 and Bacillus sp. (1301) resulted in a root diameter of 13.81 and 13.06%, respectively, larger than that of the control treatment. The use of these multifunctional microorganisms was efficient for promoting the root development of rice seedlings.